Evaluation of Bacillus sphaericus bioinsecticide produced with white soybean meal as culture medium for the control of Culex (Culex) quinquefasciatus Avaliação do bioinseticida de Bacillus sphaericus, produzido com meio de cultivo de farelo branco de soja no controle de Culex (Culex) quinquefasciatus - André L. A. Melo; Carlos R. Soccol; Vanete Thomaz-Soccol; Miodeli Nogueira Jr.S (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
Bioinsecticides are shown to be useful in control programs to prevent several diseases, based on their specificity and efficiency against insect vectors. In the current study a bioinsecticide based on Bacillus sphaericus was produced using a white soybean culture medium and applied to larvae of Culex quinquefasciatus, the susceptible species, and Aedes aegypti, the refractory species used as the negative control. Efficacy was compared with that of the product fermented with the Luria Bertani (LB) reference medium. The experiments showed that C. quinquefasciatus was highly susceptible to the product prepared with white soybean meal, reaching 100% larval mortality even at 10mg/L, while A. aegypti failed to reach 70% mortality at a concentration of 1g/L. By comparison with the reference medium, the proposed culture medium showed high larvicidal power, reaching a LD90 of 2.26mg/L, while 4.37mg/L was needed for the LB medium to achieve the same mortality rate. Cost comparison between the formulations favored the use of the bioinsecticide produced with white soybean meal. After factoring in the LD90 value, the cost ratio favored the new raw material by nearly 1:220. A utilização de bioinseticidas tem se mostrado útil aos programas de prevenção de diversas enfermidades devido a sua especificidade e eficiência contra insetos vetores. No presente trabalho, o bioinseticida de Bacillus sphaericus foi produzido com um meio de cultivo composto de farelo branco de soja e aplicado em larvas de Culex quinquefasciatus, espécie susce-tível, e Aedes aegypti, espécie refratária, usada como controle negativo. O desempenho foi comparado com o do produto fermentado com o meio referência Luria Bertani (LB). Os experimentos constataram que C. quinquefasciatus apresentou uma alta suscetibilidade ao produto produzido com farelo branco de soja, alcançando mortalidade de 100% mesmo na diluição de 10mg/L, enquanto A. aegypti não atingiu 70% na concentração de 1g/L. Quando comparado com o meio referência, a formulação proposta proporcionou um alto poder larvicida, alcançando uma DL90 de 2,26mg/L, ao passo que LB precisou de 4,37mg/L para a mesma mortalidade. A comparação do custo das formulações favoreceu o bioinseticida produzido com o meio farelo branco de soja. Considerando os valores de DL90, a relação do custo das matérias-primas ficou próxima de 1:220.